Kebijakan Kontroversial Menteri Daoed Joesoef 1978-1983: Perubahan Tahun Ajaran dan Libur Bulan Ramadhan - Amalia Solihat; Abdul Syukur; Kurniawati (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2020)
This study aims to determine the policy changes in the School Year and Ramadhan Holidays at primary and secondary education. The research method used is the historical method with a descriptive narrative approach. The historical method consists of four steps namely heuristics, verification, interpretation and historiography. Data collection through interviews, studies and literature. The results of the study concluded that the policy issued by Minister Daoed Joesoef through Minister of Education and Culture Decree No. 0211 / U / 1978 concerning the School Academic Year System is effective for the process of implementing education in terms of improving the quality of education. The issuance of the decree changed the school year school system from January to July. If in 1978 the new school year system began from January to December, then in 1979 the new school year system began from July to June 1980. The policy resulted in the extension of study time from January 1978 to June 1979. These two policies have been debated by various parties who disagree with the policies. Daoed Joesoef's economic, political and personality conditions contributed to the controversial policies of 1978-1983. Penelitian ini bertujuan untuk mengetahui kebijakan Perubahan Tahun Ajaran dan Libur Bulan Ramadhan di jenjang pendidikan dasar dan menengah. Metode penelitian yang digunakan yaitu metode sejarah dengan pendekatan deskriptif naratif. Metode sejarah terdiri dari empat langkah yaitu heuristik, verifikasi, interpretasi dan historiografi. Pengumpulan data melalui wawancara, studi dan literatur. Hasil penelitian menyimpulkan bahwa kebijakan yang dikeluarkan oleh Menteri Daoed Joesoef melalui Surat Keputusan Menteri pendidikan dan Kebudayaan No. 0211/U/1978 tentang Sistem Tahun Ajaran Sekolah efektif bagi proses pelaksaan pendidikan dalam hal peningkatan mutu pendidikan. Keluarnya Surat keputusan tersebut merubah sistem tahun ajaran sekolah dari bulan Januari ke bulan Juli. Dua kebijakan tersebut menjadi perdebatan berbagai pihak yang tidak setuju dengan kebijakan tersebut. Kondisi ekonomi, politik dan kepribadian Daoed Joesoef turut mewarnai kebijakan kontroversial 1978-1983.